Understanding molecular self-assembly of a diol compound by considering competitive interactions. Issue 39 (22nd September 2016) - Arado, Oscar Díaz; Luft, Maike; Mönig, Harry; Held, Philipp Alexander; Studer, Armido; Amirjalayer, Saeed; Fuchs, Harald
Abstract : With a combination of scanning tunneling microscopy and density functional theory, effects on molecular self-assembly involving two distinct chemical groups were investigated. Abstract : With a combination of scanning tunneling microscopy and density functional theory, effects on molecular self-assembly involving two distinct chemical groups were investigated. We analyzed the influence of the individual functional units in the adsorbate and extracted the dominating contributions to the adsorption behaviour. The viability of such a systematic approach to study self-assembled structures by considering the interplay between substrate effects and molecular design is demonstrated.